2019
DOI: 10.1105/tpc.19.00110
|View full text |Cite
|
Sign up to set email alerts
|

AtTRAPPC11/ROG2: A Role for TRAPPs in Maintenance of the Plant Trans-Golgi Network/Early Endosome Organization and Function

Abstract: The dynamic trans-Golgi network/early endosome (TGN/EE) facilitates cargo sorting and trafficking and plays a vital role in plant development and environmental response. Transport protein particles (TRAPPs) are multi-protein complexes acting as guanine nucleotide exchange factors and possibly as tethers, regulating intracellular trafficking. TRAPPs are essential in all eukaryotic cells and are implicated in a number of human diseases. It has been proposed that they also play crucial roles in plants; however, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 120 publications
(217 reference statements)
2
42
1
1
Order By: Relevance
“…The presence of the homologs of the four animal TRAPPIII-specific subunits (TRAPPC8, TRAPPC11, TRAPPC12, and TRAPPC13) in the AtTRS33 interactome but not the TRIPP interactome suggests the existence of both TRIPP-containing TRAPPII complex and an equivalent of TRAPPIII complex that excludes TRIPP. Indeed, in accordance with our results, a recent IP-MS using AtTRAPPC11 has confirmed the presence of a TRAPPIII complex in Arabidopsis (Rosquette et al, 2019). Our Y2H data indicates that TRIPP interacts with the two TRAPPII-specific subunits TRS120 and TRS130, further corroborating TRIPP association with the TRAPPII complex.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of the homologs of the four animal TRAPPIII-specific subunits (TRAPPC8, TRAPPC11, TRAPPC12, and TRAPPC13) in the AtTRS33 interactome but not the TRIPP interactome suggests the existence of both TRIPP-containing TRAPPII complex and an equivalent of TRAPPIII complex that excludes TRIPP. Indeed, in accordance with our results, a recent IP-MS using AtTRAPPC11 has confirmed the presence of a TRAPPIII complex in Arabidopsis (Rosquette et al, 2019). Our Y2H data indicates that TRIPP interacts with the two TRAPPII-specific subunits TRS120 and TRS130, further corroborating TRIPP association with the TRAPPII complex.…”
Section: Discussionsupporting
confidence: 93%
“…SNARF-1 staining (Thermo Fisher, C1270) was performed using a protocol adapted from Rosquete et al, 2019. Briefly, 1 μL of 10 mM SNARF-1 was diluted in 1 mL of CoroNa Green incubation buffer, and sections are incubated in this solution in the dark for 3 h at room temperature before imaging (Rosquete et al, 2019). Suberin staining was performed using a protocol adapted from Naseer et al (Naseer et al, 2012).…”
Section: Fluorescent Staining and Microscopymentioning
confidence: 99%
“…Sanderfoot et al, 2001;Uemura et al, 2004). SYP61 predominantly localized to the TGN/EE, but recent studies reported that SYP61 also localized to the plasma membrane and the vacuolar membranes under specific conditions (Gendre et al, 2013;Hachez et al, 2014;Rosquete et al, 2019). In addition, SYP61 colocalized with the LE markers, an R-SNARE VAMP727 and a RAB GTPase ARA7/RABF2b, to form the hybrid compartment of the TGN/EE and the LE involved in the endocytosis of FLS2 receptor protein after flg22 treatment (Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 97%